Indo-Pak Relations : Twists and Turns from Partition to Agra Summit and Beyond - Gehlot, N. S. and Satsangi, Anu (New Delhi Deep & Deep Publications Pvt. Ltd., 2004)
Book Summary of Indo-Pak Relations : Twists & Turns From Partition To Agra Summit & Beyond This book focuses on the twists and turns in Indo-Pak relations, as well as the fallout of the 11th September, 2001 terror attacks in the US, followed by the war on Iraq under the US-led coalition forces at he cost of UN. The authors' analysis is that the changing world scenario hasn't helped India and Pakistan to improve their ties. This is the most unfortunate development in South Asia.
Include Bibliography and Index.
Twists and Turns from Partition to Agra Summit and Beyond
Keywords: Summit meetings -- India--Agra -- Pakistan -- India -- Diplomatic relations